POLITIK HUKUM KEJAKSAAN REPUBLIK INDONESIA DALAM PEMBERANTASAN KORUPSI PADA ERA PEMERINTAHAN PRESIDEN JOKO WIDODO - Pandoe Pramoe Kartika; Andrie Dwi Subianto; I Made Agus Mahendra Iswara (Jurnal Hukum Saraswati (JHS), 2019)
The Attorney General's Office of the Republic of Indonesia as one of the law enforcers who has main duties and functions in law enforcement, one of which is related to eradicating corruption. Seeing the importance of the position of the prosecutor in the special law enforcement in eradicating corruption, it is important to conduct a study of the Politics of Law to eradicate corruption in the prosecutor's office, especially during the administration of President Joko Widodo. The conclusions of this paper are the first Political Law to eradicate corruption in the era of President Jokowi's administration has similarities with previous era governments, including the issuance of regulations on eradication and prevention of corruption, the formation of adhoc teams, and several regulations in the Jokowi era that curb corruption eradication. Secondly, the Republic of Indonesia's Attorney General's Office as a government agency indirectly in making its legal policies requires policies taken by the government. The prosecutors' policies in eradicating corruption are in line with the government's intentions, namely the formation of the TP4 Team, and the emphasis on handling cases that are of legal equality which make the basis for consideration on the principle of benefit and the principle of proportionality to support the government's development and smooth running program.